Small great things [compact disc, unabridged] : a novel - Picoult, Jodi, 1966- (Books on Tape ; Random House Audio, 2016)
Ruth Jefferson is a labor and delivery nurse at a Connecticut hospital with more than twenty years' experience. During her shift, Ruth begins a routine checkup on a newborn, only to be told a few minutes later that she's been reassigned to another patient. The parents are white supremacists and don't want Ruth, who is African American, to touch their child. The hospital complies with their request, but the next day, the baby goes into cardiac distress while Ruth is alone in the nursery. Does she obey orders or does she intervene?